Ultrasonic Assisted Extraction of Phenolic and Flavonoid Content from Orthosiphon Stamineus Leaves - Sook, Fun Pang; M. M., Yusoff; Luqman Chuah, Abdullah; Jolius, Gimbun (Asia Pacific Publishing, 2015)
This paper presents a combined effect of ultrasonic assisted extraction and solvents of varying polarities on phenolic compound extraction from O. stamineus. The polyphenol content in the plant extracts was analysed using Singleton’s method and aluminium chloride colorimetric assay. The results suggest that the polyphenol extraction from O. stamineus is affected by the solvent type. The highest phenolic content of 168.8 mg GAE/g DW was obtained from ultrasonic assisted extraction (UAE) using 70% aqueous methanol and 70% aqueous propanol solvent. The highest total flavonoid content of 185.3 mg QE/g DW was obtained using 70% aqueous propanol. The phenolic acid and flavonoid yield increased with extraction time, however, extraction beyond 120 min or at a temperature higher than 60°C induced degradation and hence reducing extraction yield.